The Influence Of Price, Product Quality And Promotion On The Purchase Decision Of Villa Banana Cake Products At The Botania Outlet Batam City - Bayu Setiadji; Andi M Lutfhi (Syntax Corporation Indonesia, 2023)
In an era where technology is so sophisticated as it is today, it triggers very tight competition in the business world, plus the Covid-19 pandemic outbreak that originated in Wuhan, China in early 2020 until today has forced business actors to work even harder. All means and efforts are made so that their business can survive or even increase and can face increasingly fierce competition. The results of this study indicate that price, product quality and promotion have a simultaneous effect on purchasing decisions. Price, product quality and promotion together will have an influence on purchasing decisions